Deuterium equilibrium time in saliva of newborn infants - Traver, Luis Ângelo Marti; Martinez, Francisco Eulógio; Ferriolli, Eduardo; Marchini, Júlio Sérgio; Monteiro, Jacqueline Pontes; Pfrimer, Karina; Sanchez, Ana Paula Michelin; De Oliveira, Thais; Ducatti, Carlos [UNESP]; Camelo Jr., José Simon (Wiley, 2009)
There is an increasing interest about the use of stable isotopes for body composition analysis in pediatrics. To ensure the success of total body water analysis by the deuterium dilution method, it is fundamental to determine the equilibrium time (plateau) of deuterium in the body fluid studied. OBJECTIVES: We report here the equilibration time of deuterium oxide in the saliva of newborns after oral intake of the isotope. METHODS: Twenty healthy term newborn infants, 10 males and 10 females, were analyzed. Saliva was collected from each newborn before the oral administration of a 100 mg/kg dose of deuterium oxide (baseline sample) and then at 1-hour intervals for 5 hours after administration. Deuterium enrichment of saliva was determined by isotope ratio mass spectrometry according to the recommendations of the International Atomic Energy Agency. RESULTS: The plateau time of deuterium in saliva occurred 3 hours after oral administration of the stable isotope. CONCLUSION: These data are essential for further studies on the body composition of newborn infants. To the best of our knowledge, this is the first study regarding the equilibration time of deuterium in the saliva of term newborns. © 2009 by European Society for Pediatric Gastroenterology, Hepatology, and Nutrition and North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition.
Keywords: Body composition; Deuterium; Newborn; Saliva; TBW